Histology of Luminal Breast Cancer - Erber, Ramona; Hartmann, Arndt (Breast Care, 2020)
Background: Invasive breast cancer (IBC) can be categorized into prognostic and predictive molecular subtypes (including luminal breast cancer) using gene expression profiling. Luminal IBC comprises a variety of histological subtypes with varying clinical and pathological features. Summary: IBC of no special subtype is the most common histological subtype in general and likewise within luminal IBC. Classical invasive lobular breast cancer, typically clustering into luminal subgroup, is characterized by discohesive growth and loss of E-cadherin expression. Infrequent, morphologically distinct luminal IBC subtypes are tubular, invasive cribriform, mucinous, and invasive micropapillary carcinomas. Breast carcinoma with apocrine differentiation, with characteristic expression of androgen receptor (AR), often clusters into the luminal AR category. Rarely, neuroendocrine neoplasms of the breast can be seen. IBC of the male breast usually matches with the luminal subtype. Key Messages: Independently from histological subtypes, invasive breast cancer (IBC) can be divided into molecular subtypes based on mRNA gene expression levels. Using this molecular subtyping, risk scores based on gene expression profiling (established for hormone receptor-positive, HER2-negative IBC), grading, and Ki-67 index, prognosis of patients with luminal breast cancer and response to chemotherapy can be predicted. In routine diagnostics, the expression of estrogen receptor (ER) and progesterone receptor (PR), HER2 status, and the proliferation rate (Ki-67) are used to determine a surrogate (molecular-like) subtype. Within luminal(-like) IBC, no special subtype and invasive lobular breast carcinoma are the most common histological subtypes. Other rare histological subtypes (e.g., tubular carcinoma) should be recognized due to their distinct clinical and pathological features.
CRIS-Team Scopus Importer:2020-07-31